Quantum wave-packet calculation of reaction probabilities, cross sections, and rate constants for Li+H+2 reaction - art. no. 244301 - Gogtas, F (Aip Publishing, 2005)
The Li+H-2(+)(upsilon,j)-> LiH(upsilon('),j('))+H+ reactive scattering has been studied by using quantum real wave-packet method. The state-to-state and state-to-all reaction probabilities for the entitled collision have been calculated. The probabilities show a smooth variation for all initial rotational quantum states. The J-shifting approximation has been employed to estimate the integral cross sections and thermal rate constants have been calculated. (c) 2005 American Institute of Physics.
Keywords: Potential-Energy Surface; Dynamics; Scattering; Chemistry; Complex; System; Lih2+